On the Approximation of Functions of the Hölder Class by Triharmonic Poisson Integrals - Zhyhallo, K. M.; Kharkevych, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We determine the exact value of the upper bound for the deviation of the triharmonic Poisson integral from functions of the Hölder class.